Lighting Fundamentals for the Undergraduate Science, Technology, Engineering and Mathematics (STEM) Student - Martin, Kevin B.; J. Mills, William (International Journal For Research In Educational Studies, 2017)
Light is the most dominant human sense and plays a very important role in how humans perceive and interact in every environment. Numerous professions benefit from an understanding of the fundamentals of light due to the ubiquitous nature of light. This paper provides a set of engaged/active experiments to help students 1) gain an understanding of the proper measurement and interpretation of light data; and 2) determine the operational characteristics and capabilities of current commercially available lighting technology. The hands-on activities and provided questions for reflective thought result in the development of critical thinking skills regarding lighting issues. To fully prepare the student prior to the experiments, preparatory research questions and resources are also provided.